High structural and molecular parameter diversity among chemicals with similar log P and log Koc values. (12th August 2020) - Smith, Carr J; Perfetti, Thomas A; Ko, Gene M; Hartigan, Suzanne B
Chemicals possessing persistence (P) and high mobility (M) can present a hazard to drinking water resources by traversing natural barriers like riverbanks and artificial barriers found in water treatment plants. If the chemical is also toxic (T), i.e. classifiable as a PMT, the agent might be of particular concern as a potential drinking water contaminant. During routine water sampling, detection and quantitation of polar substances with high mobility can be problematic. The German Environment Agency (UBA) is considering the use of the Log Koc value as a proxy for mobility (M). Log Koc is related to Log P by the equation Log Koc = 0.69 Log P + 0.22. In this study, we demonstrate that chemicals with log P values at or very close to 2.0, 3.0 or 4.0 (and their concomitant log Koc values) can vary significantly in their chemical structures, molecular weights, molar volumes, and calculated molar refractivity (CMR), which is related to the mean polarizability of a molecule. The large degree of potential diversity in chemical structure and molecular parameters related to chemical behavior at a particular log P or log Koc value suggests that log Koc might not contain enough information to function as a standalone surrogate for the mobility (M) of a chemical, i.e. as related to its ability to move from a drinking water resource through the water plant purification process.